2022
DOI: 10.4081/ija.2022.2121
|View full text |Cite
|
Sign up to set email alerts
|

Interregional comparative analysis of farmers’ perceptions and expectations of climate change

Abstract: This study looked into the relationship and effects of agricultural activities in different regions of Turkey on climate change. This study aims to determine farmer awareness of climate change and its effects, as well as farmer adaptation capabilities in different regions of Turkey against climate change, and to develop extension and policy tools based on the findings. Data were collected through face-to-face surveys with farmers in the provinces where the research was conducted. In this context, a proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It was dedicated that all melon farmers within the scope of the research had social security. Kaya and Bay (2020); Kaya and Bostan Budak (2022); Acıbuca et al, (2022) stated that the majority of farmers have social security. de Mello (2000) Melon farmers depend on the income generated from the crop to send their children to school, provide shelter and improve their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was dedicated that all melon farmers within the scope of the research had social security. Kaya and Bay (2020); Kaya and Bostan Budak (2022); Acıbuca et al, (2022) stated that the majority of farmers have social security. de Mello (2000) Melon farmers depend on the income generated from the crop to send their children to school, provide shelter and improve their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Yılmaz et al, (2011) seasonal price fluctuations are one of the major factors that limit the melon production in Türkiye. Acıbuca et al, (2022) reported that chemical inputs used in agriculture should be reduced and used carefully. Yılmaz et al, (2011) reported the necessity of extension activities in the fight against pests and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most critical issues of the 21st century, alongside the greenhouse gas effect and global warming, is an atmospheric event that occurs with the destructive interaction of soil, human, and climate elements [12][13][14]. Many existing studies state that 25% of global warming is caused by agricultural activities [15].…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect of climate change that is complementary to the physical environmental effects of climate change is the perception of such changes by farmers. Acibuca et al (2022) explored farmer awareness of climate change impacts. They evaluated farmers' adaptation capacity in different regions of Turkey.…”
mentioning
confidence: 99%